Safety and immunogenicity of heterologous recombinant protein subunit vaccine (ZF2001) booster against COVID-19 at 3–9-month intervals following two-dose inactivated vaccine (CoronaVac) - Yuting Liao; Yingping Chen; Bo Chen; Zhenzhen Liang; Xiaosong Hu; Bo Xing; Juan Yang; Qianhui Zheng; Qianhui Hua; Chuanfu Yan; Huakun Lv (Frontiers in Immunology, 2022)
BackgroundIn response to SARS-CoV-2 mutations and waning antibody levels after two-dose inactivated vaccines, we assessed whether a third dose of recombinant protein subunit vaccine (ZF2001) boosts immune responses.MethodsAn open-label single-center non-random trial was conducted on people aged 18 years and above at five sites in China. All participants received a two-dose inactivated vaccine (CoronaVac) as their prime doses within 3–9 months of the trial. Primary outcomes were safety and immunogenicity, primarily the geometric mean titers (GMTs) of neutralizing antibodies to live wildtype SARS-CoV-2.ResultsA total of 480 participants (median age, 51; range 21–84 years) previously vaccinated with two-dose CoronaVac received a third booster dose of ZF2001 3–4, 5–6, or 7–9-months later. The overall incidence of adverse reactions within 30 days after vaccination was 5.83% (28/480). No serious adverse reactions were reported after the third dose of ZF2001. GMTs in the 3–4-, 5–6-, and 7–9-month groups before vaccination were 3.96, 4.60, and 3.78, respectively. On Day 14, GMTs increased to 33.06, 47.51, and 44.12, respectively. After the booster, GMTs showed no significant difference among the three prime-boost interval groups (all P>0.05). Additionally, GMTs in older adults were lower than those in younger adults on Day 14 for the three groups (P=0.0005, P<0.0001, and P<0.0001).ConclusionHeterologous boosting with ZF2001 was safe and immunogenic, and prime-boost intervals did not affect the immune response. The immune response was weaker in older than younger adults.